Evaluation of the More Doctors Program from the perspective of users: More Doctors Program - Souza Gleriano, Josué; Conceição Martins , Lourdes; Krein, Carlise; Dias Pedreschi Chaves, Lucieli (Journal of Health Care, 2023)
Introduction: The More Doctors Program (PMM) contributed to expand the coverage of Primary Health Care (PHC). Objective: To analyze, according to the experience of users, challenges and benefits of pmm. Method: Evaluation research of concomitant mixed method conducted in Tangará da Serra - Mato Grosso, with users registered in the area of coverage of family health units that had in their team doctors of the PMM, during the period from 2016 to 2018. For quantitative data, descriptive analysis was generated using ibm spssÂ® software version 21. Qualitative Solutions Research NVivoÂ® 10 software was used for thematic analysis, which provides presentation in two categories, "PMM: from distrust to recognition through medical practice" and "User-friendly practice and bonding: two-way". The mixing of the data explored the completeness of the information collected. Results: 1036 users participated, in favor of the Program, reporting overcoming language communication; recognition in improving access to medical consultation with decreased waiting time. There is satisfaction with the practice of the professional, arouses mutual contributions between users and the professional, expanding possibilities of co-responsibility with health in the territory. Conclusion: It is revealed subsidies from the PMM in the municipality, which designed the expansion of coverage with recognition of its users, greater possibility of effecting attributes of PHC and fostering the organization of a care network, at the same time the challenge of sustainability of this proposal due to the dependence on cooperation of the Program.